House Advantage or House of Cards? Stacking the Deck for Data Videos Leads to Null Results. - Rogers, Jen.; Shen, Leixian.; Mosca, Ab.; Peck, Evan.; Li, Mingwei.; Hakone, Anzu.; Potter, Kristi.; Chang, Remco. (Tufts University. Tisch Library., 2025)
Keywords: Data Video, Static Visualization, Comprehension.; Topic: Human-centered computing / Information visualization; ACM Open.